2010
DOI: 10.1143/apex.3.011003
|View full text |Cite
|
Sign up to set email alerts
|

Optical Polarization Characteristics of InGaN Quantum Wells for Green Laser Diodes on Semi-Polar {20\bar21} GaN Substrates

Abstract: The polarization characteristics of InGaN quantum wells on semi-polar {2021} GaN substrates were investigated to reveal the advantageous laser stripe orientation. The polarization ratio exhibited a gradual increase within the range of around 0.2 to 0.3 with an increase in the emission wavelength from 400 to 550 nm under a low current density of 7.4 A/cm2. In addition, the dependence on a current density was quite small up to 0.74 kA/cm2. These results suggest that the laser stripe perpendicular to the a-axis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 23 publications
(35 reference statements)
3
52
0
Order By: Relevance
“…While this peak wavelength dependence was similar to that of the m-plane LDs [35], the switching phenomenon, which has been observed for f1 1 2 2g InGaN QWs [28,36], did not occur. Since f2 0 2 1g InGaN QWs exhibit positive polarization ratios at high In contents as well as at high current densities [19], it is concluded that a laser stripe along the ½1 0 1 4 direction is more advantageous than that along the ½1 2 1 0 direction for LDs on the f2 0 2 1g planes. In order to verify this conclusion, we fabricated two green LDs having orthogonal stripe orientation from epitaxial wafers with equivalent PL properties.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…While this peak wavelength dependence was similar to that of the m-plane LDs [35], the switching phenomenon, which has been observed for f1 1 2 2g InGaN QWs [28,36], did not occur. Since f2 0 2 1g InGaN QWs exhibit positive polarization ratios at high In contents as well as at high current densities [19], it is concluded that a laser stripe along the ½1 0 1 4 direction is more advantageous than that along the ½1 2 1 0 direction for LDs on the f2 0 2 1g planes. In order to verify this conclusion, we fabricated two green LDs having orthogonal stripe orientation from epitaxial wafers with equivalent PL properties.…”
Section: Resultsmentioning
confidence: 98%
“…Employment of the f2 0 2 1g GaN substrates provides several advantages including the small blue shift resulting from the reduced internal electric fields and the homogeneous growth of InGaN QWs even at high In concentrations. Adding to these beneficial effects, we reported that the optical anisotropy of f2 0 2 1g InGaN QWs also affects the lasing properties [19]. Very recently, the 506.4 and 444.7 nm pulsed lasings were also demonstrated on the semi-polar f2 0 2 1g plane and the similar f3 0 3 1g plane, respectively, with AlGaN cladding free structures [20,21].…”
Section: Introductionmentioning
confidence: 95%
“…Besides, (1122) oriented films appear to be mostly smooth [9]. Effective long-wavelength emission of InGaN/GaN LEDs grown on the (2021) substrate and on the (2021) substrate has been reported in many papers (see, e.g., [17][18][19] and [20][21][22], respectively). However, taking into account aggregate results of the above analysis, we have decided to choose the (1122) InGaN/GaN LEDs.…”
Section: Designing Of Nitride Leds With Reduced Polarization Effectsmentioning
confidence: 97%
“…For example, semipolar planes such as the (20 21) plane, which is miscut by 15 from the m-plane (75 from the c-plane), have attracted significant interest due to their promising performance in the green region of the spectrum. [18][19][20][21][22] In addition, GaN-based QW structures grown on vicinal c-plane substrates with small crystal angles (h ¼ 0 -40 ) tilted with respect to the (0001) facets are expected to have several advantages. For example, Yamaguchi theoretically showed that even a small inclination of a c-plane substrate drastically changes optical polarization properties.…”
Section: Introductionmentioning
confidence: 99%